2022
DOI: 10.3390/pharmaceutics14081621
|View full text |Cite
|
Sign up to set email alerts
|

Orally Dispersible Dosage Forms for Paediatric Use: Current Knowledge and Development of Nanostructure-Based Formulations

Abstract: The paediatric population has always suffered from a lack of medicines tailored to their needs, especially in terms of accurate dosage, stability and acceptability. Orodispersible dosage forms have gone through a resurrection as an alternative to liquid formulations or fractioned solid formulations, although they are still subject to several inconveniences, among which the unpleasant taste and the low oral bioavailability of the API are the most significant hurdles in the way of achieving an optimal drug produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 153 publications
(281 reference statements)
0
12
1
Order By: Relevance
“…31 Many excipients are used in the formulation of ODTs to ensure a good taste profile because they have a longer oral residence than other dose forms. 32 The overall mean pH for the total sample of ODTs was found to be 6.11 AE 0.88, which was less than that reported by Maguire et al and Arora et al (8.09 and 7.49, respectively). 33,34 We found that the pH was lowest in antimicrobials which were similar to Maguire et al and Arora et al (4.29, 5.7).…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…31 Many excipients are used in the formulation of ODTs to ensure a good taste profile because they have a longer oral residence than other dose forms. 32 The overall mean pH for the total sample of ODTs was found to be 6.11 AE 0.88, which was less than that reported by Maguire et al and Arora et al (8.09 and 7.49, respectively). 33,34 We found that the pH was lowest in antimicrobials which were similar to Maguire et al and Arora et al (4.29, 5.7).…”
Section: Discussioncontrasting
confidence: 57%
“…4 Because of anticipated stability problems with liquid media, like degradation and microbiological contamination, this formulation is not appropriate for all pharmacologically active ingredients. 4 Patient-friendly dose forms such as Orodispersible tablets (ODT) were developed to overcome this. 4 ODT are "uncoated tablets that rapidly disintegrate in the oral cavity before being swallowed, turning into a solution or a suspension using the existing saliva and rarely requiring the use of external liquids such as water."…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations